PHARMACOMETRIC MODELS - A MODERN TOOL FOR QUANTIFYING VARIABILITY AND INDIVIDUALIZING DRUG DOSING REGIMENS - Vučićević, Katarina (Archives of Pharmacy, 2023)
Pharmacometric models are a powerful tool and an essential aspect of modern pharmaceutical research, drug development and clinical practice. They provide a quantitative framework for understanding the complex interaction between drug characteristics, patients, and diseases, enabling the selection of drugs and dosing regimens to optimize therapeutic outcomes (1). Patients vary in their response to medications due to genetic, physiological, clinical, or environmental factors. Different responses to therapy can be of pharmacokinetic, pharmacodynamic, or disease-related nature, indicating that one dose does not fit all patients. Addressing the variability is essential for stratifying dosing regimens for specific patient populations. One of the key advantages of pharmacometric models lies in their ability to distinguish different levels of variability in drug behavior, especially in quantifying and mathematically describing the sources of interindividual variability, as well as predicting how different patients will react to the drug. This knowledge is invaluable for specific patient populations to identify optimal dosing regimens that provide maximum efficacy with minimal side effects. Model-informed dosing is significant in pediatrics, elderly, critically ill patients, or patients with impaired liver/kidney function, where a one-size-fits-all dosing recommendation is often not applicable (2). The lecture will present research results where pharmacometric models contribute to new insights and improve drug development by unlocking the potential of personalized medicine.